Measuring Equivalent Cohesion Ceq of the Frozen Soils by Compression Strength using Kriolab Equipment - Lemenkov, Vasiliy; Lemenkova, Polina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Current paper presents the results of the experimental analysis on permafrost uppermost soil samples with various physical properties (moisture, porosity) tested with varied external pressure and time. The aim of this work is to test properties of the soil samples intended for the construction of buildings, railways and objects of civil infrastructure by modeled external pressure, data visualization and analysis.
Keywords: equivalent cohesion; modeling; deformation; moisture; pressure; soils; geotechnical engineering; experiment; data visualization; pomiar spójności; gleba; odkształcenia; wytrzymałość na ściskanie; eksperyment; inżynieria geotechniczna